Miniature capillary array device for isoelectric focusing electrophoresis - LI SI; CAO CHENGXI; FAN LIUYIN; ZHANG WEI; GUO CHENGANG (2011)
The invention relates to a miniature capillary array device for isoelectric focusing electrophoresis (IEF) in the technical field of biochemical engineering. The device consists of an array type electrophoresis tank and miniature capillaries, wherein the array type electrophoresis tank has two symmetrical parts; a groove array is carved on the array type electrophoresis tank; and the miniature capillaries are arranged in the groove array. One pair or multiple pairs of the array devices of the invention are selected to perform IEF simultaneously according to need and the separation flux of theprotein sample can be from dozens of tubes to hundreds of tubes. The diameter and length of the miniature capillaries in the device are shorter, thus the IEF time and cost can be effectively reduced.